(untitled) (Aporte Santiaguino, 2019)
Currently, irresponsible dog ownership is perceived, we observe a lot of these wandering on public roads in cities, Huaraz is no stranger to this problem, the dogs cause discomfort, forming packs that attack people, spread garbage, litter the streets , parks and gardens with urine and feces, which are sprayed and dispersed in the air causing diseases. The objective was to determine the relationship between stray dogs and pollution of public roads in the city of Huaraz, Ancash - Peru 2017. Correlation studies, doing: Counting of dogs, being the population and sample all dogs; survey to family heads, population and sample 7460 and 366 dwellings respectively; coprological analysis, population all feces and sample 153 fresh feces for convenience in the six neighborhoods. In addition, municipal and health authorities were interviewed. A total of 1239 stray dogs were determined; 76, 0 % of all surveyed raised dogs with a p value of 0, 000 indicating a signicant relationship between stray dogs and pollution of public roads, it was found that 15, 7 % of Ancylostoma spp, 3, 3 % of Diphilidiun caninum and 1, 3 % of Giardia spp by the method of direct observation andWillis